A Review of the Collaborative Development of Large-Scale Medical Information Systems in China Based on Data Security Policy - Tang, Chenshuang; Pan, Jiawei; Wu, Jun; Xu, Zhongcheng (International Journal of Computer Science and Information Technology, 2024)
Although in recent years China's governments at all levels and medical administrative bodies have attached great importance to the protection of health and medical big data, and taken various measures to promote the standardized use and effective protection of data, however, China's large population base, health care resources allocation has a strong complexity, so health care data show significant high-frequency changes and complex and diverse characteristics, patients are also in the main links of treatment, payment, and so on, the authenticity of the data are very high requirements. In such a special social environment, from the perspective of both theory and practice, to maximize the application of data in the medical information system while trying to reduce security risks, in the background of relative security to achieve the equilibrium of data utilization and data security, which is worth studying.